THE IMPLEMENTATION OF RISK MANAGEMENT OF FOREIGN EXCHANGE INVESTMENT AT PT. BEST PROFIT FUTURES MALANG - Puspitasari, Ulfa (Manajemen Bisnis, 2018)
This study aimed (1) to determine the risk of forex investments and (2) to figure out the implementation of risk management on forex. This study used descriptive method to examine a brokerage firm located in Malang named PT Best Profit Future Malang. Based on the results, it was found that the risks in forex investment were a floating risk of market circumstances, price change, overnight, interest rates and political event. The analysis used to determine the volatility of the forex market were technical and fundamental analysis. Technical analysis used an accurate historical rates and calculations whereas fundamental analysis used information and market news. Forex investment had a high investment risk if market volatility was not favorable, so the risk management was urgently required. Therefore, there were five risk managements; hold, aver4age, limit loss/locking, switching, and cut loss.